2019
DOI: 10.1002/brb3.1370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acupuncture at ST36 on motor cortical excitation and inhibition

Abstract: Background Acupuncture at Zusanli (ST36) is often used to facilitate motor recovery after stroke. However, the effect of acupuncture at ST36 on motor cortical excitation and inhibition remains unclear. This study aimed to explore the effect of acupuncture at ST36 on motor cortical excitation and inhibition. Methods Twenty healthy volunteers were recruited to receive acupuncture treatment. We selected the acupoint ST36 and its respective sham point as the experimental acupoint. Transcranial magnetic stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…Therefore, acupuncture at PC6 can produce a protective cardiovascular effect and increase gastric motility related to the inhibition of GABA. Acupuncture at ST36 during the remaining needle phase can increase motor cortical excitation and reduce motor cortical inhibition through transcranial magnetic stimulation 9 . A transcriptomic analysis in mice revealed that EA at ST36 involves the GABAergic neurotransmission network of the brain 10 .…”
mentioning
confidence: 99%
“…Therefore, acupuncture at PC6 can produce a protective cardiovascular effect and increase gastric motility related to the inhibition of GABA. Acupuncture at ST36 during the remaining needle phase can increase motor cortical excitation and reduce motor cortical inhibition through transcranial magnetic stimulation 9 . A transcriptomic analysis in mice revealed that EA at ST36 involves the GABAergic neurotransmission network of the brain 10 .…”
mentioning
confidence: 99%
“…It was reported in a study that stimulation of ST 36 with using anatomical tracers revealed that there is a specific relationship and connection between the central nervous system (CNS) and the ST 36. Additionally, it was demonstrated that acupuncture therapy at ST36 alleviated pain, reduced gastric dysrhythmia, and improved stomach emptying, which were mainly mediated by the neuro-transmitters pathways and opioids pathways [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 41 In addition, Zusanli, a main acupoint of the “stomach meridian,” has been reported to promote recovery from neurologic diseases. 42 In our previous study, we reported that EA pretreatment with Hegu, Neiguan, and Zusanli significantly alleviated postoperative cognitive decline in geriatric patients with silent lacunar infarctions 15 and in patients following spine surgery. 43 In the current study, we found that EA pretreatment with Hegu, Neiguan, and Zusanli in aged rats also significantly increased crossing platform times in the Morris maze test and elevated the time with a novel object in a model of tibial fracture surgery.…”
Section: Discussionmentioning
confidence: 87%